Toni Morrison [videorecording (DVD)] : the pieces I am - Guzman, Sandra; Morrison, Toni; Als, Hilton; Davis, Angela Y. (Angela Yvonne), 1944-; Lebowitz, Fran, 1963-; Mosley, Walter; Winfrey, Oprah (Magnolia Home Entertainment, 2019)
An artful and intimate meditation on the life and works of the acclaimed novelist. From her childhood in the steel town of Lorain, Ohio to '70s-era book tours with Muhammad Ali, from the front lines with Angela Davis to her own riverfront writing room, Toni Morrison leads an assembly of her peers, critics, and colleagues on an exploration of race, America, history and the human condition as seen through the prism of her own literature.